Mergers and Alliances in Higher Education: International Practice and Emerging Opportunities - Curaj, Adrian; Georghiou, Luke; Cassingena Harper, Jennifer; Egron-Polak, Eva (Springer Nature, 2015)
Higher Education; Educational Policy and Politics; International and Comparative Education